PEMODELAN PENINGKATAN KEHANDALAN DENGAN METODE ROOT CAUSE ANALYSIS DAN FMEA PADA PERUSAHAAN PEMBANGKIT LISTRIK - Ferry Anggita Erdianto (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
XYZ is a company engaged in the generation of electrical energy. Reliability for powergeneration companies is very vital for the company's performance appraisal is based on the readinessof the unit to generate electricity load demand PLN (State Electricity Company). To support thereliability of the company has designed a system that is based on the reliability maintenance (RCM).RCM application at PT XYZ is dominated by mostly preventive maintenance based on time and baseline.Meanwhile failures still occur marked by numerous corrective maintenance that still occur on criticalequipment, causing derating production unit. Besides the efficiency of preventive maintenance is alsodoubtful, the amount of PM task that has become a waste of maintenance costs. The pattern of effectivemaintenance necessary to minimize disturbance.As a baseline, the analysis Root Cause Analysis is required to determine the prioritymaintenance. After that increase reliability by using Failure Mode and Effect Analysis (FMEA) wasconducted with a focus on the criteria of occurence, severity, and detection to determine the RiskPriority Number (RPN). To enhance decision-making systems have used system analysis history datainterference as well as MTBF and MTTR. Result of the merger of these methods are known to determinethe behavior maintenance task-a task that really affect the reliability of the unit.